PSYCHOLOGICAL CHARACTERISTICS OF PATIENTS SUFFERING FROM SKIN DISORDERS: SKIN DISORDERS - Ishika Ghosh; Suchismita Sinha (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2023)
Background: Dermatology holds a unique place among the other clinical specialties due to the "visibility" of the skin organ. Psycho dermatology focuses on the interaction between the mind and skin, based on the bio-psycho-social disease model in psychosomatics. It focuses on the complex, non-linear interactions between biological, psychological, and social factors in the pathogenesis of skin diseases. The present research work aims to assess the psychological characteristics of patients suffering from skin disorders- eczema and psoriasis. Method: A sample of 90 individuals was divided into three groups: eczema patients, psoriasis patients, and control group. Participants were administered several tools and effective results were found out after statistical analyses. Results: Significant differences between the three groups, with respect to coping styles, perceived stress, locus of control, and anxiety were demonstrated. On the other hand, in Psoriasis patients’ group, significant relationships of Coping Styles and Perceived Stress with Locus of Control and Anxiety were found out. In Eczema patients’ group, a significant relationship of coping styles and perceived stress with locus of control was found out; a significant relationship between anxiety and self-blame coping style and between locus of control and trait anxiety were also found out. Conclusion: The study reveals individuals with skin disorders experience negative psychological symptoms such as, high perceived stress, high anxiety, and negative coping styles. Psycho dermatology treatments can address these factors for a holistic healthcare approach.